Teacher's guide for unit 3 of the English Curriculum, First Grade - Vargas Solís, María Antonieta (2019)
The teacher's guide is a compilation of teaching ideas, songs, pictures, and activities to create meaningful tasks based on the English Curriculum for primary English teachers at Ministerio de Educación Pública in Costa Rica. It aims at supporting the process of planning and understanding the curriculum based on the Action-Oriented Approach. First, it details how to plan each step, then the plans and materials are provided for a whole unit.